Faktor-Faktor yang Mempengaruhi Belanja Daerah pada Pemerintah Provinsi Indonesia - Evada Dewata; RA. Munawaroh; Armaini, Rosy (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research was carried out in order to achieve the aim of understanding the factors that influence Regional Expenditures in Provincial Governments in Indonesia. The data used is secondary data sourced via the BPK RI website. The focus of this research covers a population of 34 provincial governments with the sampling technique used is a saturated sample with 170 observation units. Data processing involves the help of the Eviews version 12 application. Data analysis uses multiple linear regression analysis with a signitificance level of 5%.The results of multiple regression analysis show that simultaneously Original Regional Income, Balancing Funds and SiLPA have a signitificant effect on Regional Expenditures. But partially, Original Regional Income and Balancing Funds have a signitificant positive influence on Regional Expenditures but SiLPA has no effect on regional Expenditures.